Using NOACs in Various Clinical Situations - Nierengarten, Mary Beth (MD Conference Express, 2014)
In a session entitled “Emergent Situations in Patients on New Oral Anticoagulants,” a panel of experts discussed the use of novel oral anticoagulants (NOACs) in various clinical situations.